Role and Importance of Information Security in a Pandemic Environment (Economics and region, 2020)
The peculiarities of the impact of the COVID-19 pandemic on the world economy, national economy and security are considered, and it is detailed that information (misinformation) in cyberspace has become the most important resource and the main instantaneous driving force. The importance of information resources in the life of society and the role of information security in ensuring the national interests of any state are emphasized. The analysis of the normative-legal base of realization of the state policy in the direction of maintenance of information security in Ukraine is carried out and the strategic priorities of increase of its level are substantiated.
Keywords: information security; COVID-19 pandemic; national security